Persistence of a T Cell Infiltrate in Human Ganglia Years After Herpes Zoster and During Post-herpetic Neuralgia - Sutherland, Jeremy P.; Steain, Megan; Buckland, Michael E.; Rodriguez, Michael; Cunningham, Anthony L.; Slobedman, Barry; Abendroth, Allison (Frontiers in Microbiology, 2019)
Varicella-zoster virus (VZV) is a human herpesvirus which causes varicella (chicken pox) during primary infection, establishes latency in sensory ganglia, and can reactivate from this site to cause herpes zoster (HZ) (shingles). A major complication of HZ is a severe and often debilitating pain called post-herpetic neuralgia (PHN) which persists long after the resolution of the HZ-associated rash. The underlying cause of PHN is not known, although it has been postulated that it may be a consequence of immune cell mediated damage. However, the nature of virus-immune cell interactions within ganglia during PHN is unknown. We obtained rare formalin fixed paraffin embedded sections cut from surgically excised ganglia from a PHN-affected patient years following HZ rash resolution. VZV DNA was readily detected by qPCR and regions of immune infiltration were detected by hematoxylin and eosin staining. Immunostaining using a range of antibodies against immune cell subsets revealed an immune cell response comprising of CD4+ and CD8+ T cells and CD20+ B cells. This study explores the immune cell repertoire present in ganglia during PHN and provides evidence for an ongoing immune cell inflammation years after HZ.